Transcriptional Control of Synaptic Plasticity by Transcription Factor NF-κB. (6th January 2016) - Engelmann, Christian; Haenold, Ronny
Abstract : Activation of nuclear factor kappa B (NF- κ B) transcription factors is required for the induction of synaptic plasticity and memory formation. All components of this signaling pathway are localized at synapses, and transcriptionally active NF- κ B dimers move to the nucleus to translate synaptic signals into altered gene expression. Neuron-specific inhibition results in altered connectivity of excitatory and inhibitory synapses and functionally in selective learning deficits. Recent research on transgenic mice with impaired or hyperactivated NF- κ B gave important insights into plasticity-related target gene expression that is regulated by NF- κ B. In this minireview, we update the available data on the role of this transcription factor for learning and memory formation and comment on cross-sectional activation of NF- κ B in the aged and diseased brain that may directly or indirectly affect κ B-dependent transcription of synaptic genes.